Establishment and Application of Peristaltic Human Gut-Vessel Microsystem for Studying Host–Microbial Interaction - Jing, Bolin; Wang, Zhuo A.; Zhang, Chen; Deng, Quanfeng; Wei, Jinhua; Luo, Yong; Zhang, Xiuli; Li, Jianjun; Du, Yuguang (Frontiers in Bioengineering and Biotechnology, 2020)
Intestinal floras influence a lot of biological functions of the organism. Although animal model are strong tools for researches on the relationship between host and microbe, a physiologically relevant in vitro human gut model was still required. Here, a novel human gut-vessel microfluidic system was established to study the host-microbial interaction. Peristaltic motion of the cells on the chip was driven by a pneumatic pump. When intestinal epithelial cells (Caco2) were co-cultured with vascular endothelial cells (HUVECs) on the peristaltic microfluidic chip, Caco2 showed normal barrier and absorption functions after 5 days cultivation, which generally took 21 days in static Transwell models. Intestinal microvilli and glycocalyx layer were seen after 4 days cultivation, and Lactobacillus casei was successfully co-cultured for a week in the intestinal cavity. A model for intestinal damage and inflammatory responses caused by E.coli was set up on this chip, which were successfully suppressed by Lactobacillus casei or antibiotic. In summary, this human gut-vessel microfluidic system showed a good potential for investigating the host-microbial interaction and the effect and mechanism of microbiome on intestinal diseases in vitro.